The Aged and the Marginal: Social Geography of Older People in Nepal - Subedi, Bhim Prasad (Himalayan Review, 2009)
Much has been written about the geographic marginality, physiographic diversity and marginalized ethnic groups in Nepal. However, very little attention is paid to a large section of population that is considered aged i.e., 60 years of age and over, most of who are marginal in physical, social and economic sense. This group has emerged noteworthy due to significant increase in life expectancy and clear decline in total fertility rate in the country. According to the population census of 2001 there are a total of 1,504,311 aged people, who constitute 6.5 percent of the total population in Nepal. Between 1991 and 2001 this group of population has increased by 3.40 percent per annum. During the same period the total population of the country has increased by 2.25 percent. This paper presents the geography of aged population in Nepal demonstrating them as marginal people in the society. Data are drawn from population census 2001 plus earlier censuses and other surveys such as labour force survey. The paper argues that aged sections of population in Nepal are not paid proper attention. In terms of earning livelihood and the physical capability, they are perceived as non-productive, socially dependent and physically weak. Their proportions are higher in the physiographically marginal areas and they are further marginalized with the deteriorating economic and security situations of the country, rural exodus of supporting young adults, changing occupation of young generation and increasing family nucleation in the society. While the proportion of the aged is higher in marginal zones of the country, the aged women, i.e., further marginal group, are growing faster in the total group of the aged. With the turn of the 21st century, the need to implement realistic programs for the welfare of this marginal group in general and those supporting the households with older people through state subsidies has become critical in Nepal. Key words: Aged, marginalization, empty nest syndrome, occupational mismatch, competing demands. The Himalayan Review 35-36 (2004-2005) 1-18